Proteomics of neurodegenerative diseases: analysis of human post‐mortem brain. Issue 4 (22nd November 2018) - Li, K. W.; Ganz, Andrea B.; Smit, August B.
Abstract: Dementias are prevalent brain disorders in the aged population. Dementias pose major socio‐medical burden, but currently there is no cure available. Novel proteomics approaches hold promise to identify alterations of the brain proteome that could provide clues on disease etiology, and identify candidate proteins to develop further as a biomarker. In this review, we focus on recent proteomics findings from brains affected with Alzheimer's Disease, Parkinson Disease Dementia, Frontotemporal Dementia, and Amyotrophic Lateral Sclerosis. These studies confirmed known cellular changes, and in addition identified novel proteins that may underlie distinct aspects of the diseases. This article is part of the special issue "Proteomics" . Abstract : Mass spectrometry based proteomics is an ideal technology to elucidate aberrant protein expression in disease‐affected brain. In this review, we describe the recent proteomics findings from brains affected with Alzheimer's Disease, Parkinson Disease Dementia, Frontotemporal Dementia, and Amyotrophic Lateral Sclerosis. Brain is collected. Proteins are digested by trypsin, and the resulting peptides are analysed by LC‐MS/MS. Results are validated by alternative means, for example immunohistochemistry. This article is part of the special issue "Proteomics" .